Effects of Vagus Nerve Stimulation in Alzheimer’s Disease: A Systematic Review and Meta-Analysis of Clinical Studies - Kamoga, Ronald; Rukundo, Godfrey Zari; Nakidde, Gladys; Adriko, Wilson; Obongoloch, Johnes; Ihunwo, Amadi Ogonda (Journal of Alzheimers Disease & Parkinsonism, 2023)
Background: The most prevalent cause of dementia, which is a significant cause of disability in the elderly, is Alzheimer's disease (AD). A large number of novel treatments have been approved to treat AD, but to date none have been able to stop the progression of the disease, and sadly they are all linked to side effects, necessitating the investigation of brain stimulation techniques in the search for an alternative potential therapy. Numerous Vagus Nerve Stimulation (VNS) investigations in Alzheimer's disease have shown variable findings, including worsening cognitive symptoms in some patients and memory improvements in others. As a result, this study will carefully analyze clinical data on VNS in AD in order to offer a summary of the overall impact of VNS on AD using the Preferred Reporting Items for Systematic analyze (PRISMA). Methods: The study will be conducted and reported in accordance to the Preferred Reporting Items for Systematic Reviews and meta-analysis (PRISMA) statement. We will include clinical studies that have documented VNS in people living with AD published by April 30th 2023. We will also include accessible grey literature about the topic. We will search different electronic data bases and search engines including PubMed, HINARI, CINAHL, EMBASE, Google Scholar, Scopus, Cochrane, ISI, mRCT, Popline, Sigle, VHL, GHAll , Psych-INFO, Africa wide information and global health using AD ; VNS, brain stimulation, and dementia as the keywords. We will use a Meta -analysis, should we find that there is no heterogeneity between included studies. Discussion: This protocol describes a systematic review of clinical studies of VNS in people living with AD conducted world-wide. Following the completion and publication of this study, we believe that the findings will provide further details about VNS as a potential therapy for Alzheimer's disease and will have an impact on practice, research, and policy in the field of dementia care.
Keywords: Alzheimer's disease; Vagus nerve stimulation; Brain stimulation; Dementia